Mongolia : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report, 2005)
This paper discusses key findings of the Ex Post Assessment of Longer-Term Program Engagement for Mongolia. The paper assesses Mongolia's progress in implementing its transition to a market economy, economic stabilization, and reform programs supported by the IMF during 1991-2004, and draws lessons for future IMF involvement. Assessment reveals that macroeconomic stability has been broadly achieved in Mongolia, with growth restored and inflation generally under control. Much of the state structure has been privatized or updated, and the economy and export base have diversified. However, the economy still remains vulnerable to shocks.